2009
DOI: 10.1677/joe-09-0118
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle deiodinase type 2 regulation during illness in mice

Abstract: We have previously shown that skeletal muscle deiodinase type 2 (D2) mRNA (listed as Dio2 in MGI Database) is upregulated in an animal model of acute illness. However, human studies on the expression of muscle D2 during illness report conflicting data. Therefore, we evaluated the expression of skeletal muscle D2 and D2-regulating factors in two mouse models of illness that differ in timing and severity of illness: 1) turpentine-induced inflammation, and 2) Streptococcus pneumoniae infection. During turpentinei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…While acute inflammation decreases muscle D3 (Kwakkel et al 2010), bacterial sepsis does not affect D3 and chronic inflammation even increases D3 expression (Kwakkel et al 2009). In critically ill patients, muscle D3 is also increased (Peeters et al 2003).…”
Section: Type 3 Deiodinasementioning
confidence: 93%
See 3 more Smart Citations
“…While acute inflammation decreases muscle D3 (Kwakkel et al 2010), bacterial sepsis does not affect D3 and chronic inflammation even increases D3 expression (Kwakkel et al 2009). In critically ill patients, muscle D3 is also increased (Peeters et al 2003).…”
Section: Type 3 Deiodinasementioning
confidence: 93%
“…In critically ill patients, muscle D3 is also increased (Peeters et al 2003). These changes seem to be independent on inflammatory pathways since neither sepsis nor chronic inflammation induces phosphorylation of the NF-kB and ERK pathways (Kwakkel et al 2009). In proliferating myoblasts, D3 functions as a survival factor by decreasing TH concentrations and suppressing TH induced FoxO3 mediated gene expression (Dentice et al 2014).…”
Section: Type 3 Deiodinasementioning
confidence: 98%
See 2 more Smart Citations
“…It was suggested that, together, these modifications in deiodinase expression could be a major factor involved in causing the low T3 concentration that is associated with NTIS. The trigger for these changes in deiodinase expression has been attributed to an increase in proinflammatory cytokines, which often occurs in NTIS (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%